(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of electroacupuncture, acupressure-massage combined with shortwave therapy on patients with simple periarthritis of the shoulder. Method: A controlled clinical trial was conducted on 60 patients with simple periarthritis of the shoulder, evaluated based on VAS, McGill-McRomi, Constant-Murley, and SPADI scales. Results: After treatment, both groups showed significant improvement in pain scores (VAS), range of motion (McGill-McRomi), and shoulder function (Constant-Murley, SPADI) (p < 0.05). However, the group that received combined shortwave therapy demonstrated superior efficacy across all assessed parameters (p < 0.05), with a good outcome rate of 93.33% compared to 50% in the control group (p < 0.05). Conclusion: The regimen of electroacupuncture, acupressure-massage combined with shortwave therapy is a safe and remarkably effective method for treating simple periarthritis of the shoulder. Keywords: Periarthritis of the shoulder, electroacupuncture, acupressure-massage, shortwave therapy, functional rehabilitation.